2022
DOI: 10.1017/s003329172100550x
|View full text |Cite
|
Sign up to set email alerts
|

Multispecies probiotic administration reduces emotional salience and improves mood in subjects with moderate depression: a randomised, double-blind, placebo-controlled study

Abstract: Background The potential antidepressant properties of probiotics have been suggested, but their influence on the emotional processes that may underlie this effect is unclear. Methods Depressed volunteers (n = 71) were recruited into a randomised double-blind, placebo-controlled study to explore the effects of a daily, 4-week intake of a multispecies probiotic or placebo on emotional processing and cognition. Mood, anxiety, positive and negative affect, sleep, salivary cortisol and serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Some strains, e.g., Bifidobacterium infantis , B. longum , and L. acidophilus , may improve mental conditions via regulating the expression of endocannabinoids or by producing and secreting neurotransmitters such as 5-hydroxytryptamine (serotonin, 5 HT), ACh, catecholamines, dopamine, histamine, GABA, glutamate (Glu), glycine, and norepinephrine in a species-dependent manner [ 56 , 108 ]. These neurotransmitters modulate signaling pathways of the local enteric nervous system and then the gut–brain axis [ 226 ]. Moreover, some probiotic strains and their metabolites reverse depressive diseases via immunomodulation.…”
Section: Probiotic Preparations In Depressionmentioning
confidence: 99%
“…Some strains, e.g., Bifidobacterium infantis , B. longum , and L. acidophilus , may improve mental conditions via regulating the expression of endocannabinoids or by producing and secreting neurotransmitters such as 5-hydroxytryptamine (serotonin, 5 HT), ACh, catecholamines, dopamine, histamine, GABA, glutamate (Glu), glycine, and norepinephrine in a species-dependent manner [ 56 , 108 ]. These neurotransmitters modulate signaling pathways of the local enteric nervous system and then the gut–brain axis [ 226 ]. Moreover, some probiotic strains and their metabolites reverse depressive diseases via immunomodulation.…”
Section: Probiotic Preparations In Depressionmentioning
confidence: 99%
“…Additionally, research involving animal subjects was not within the scope of this review and was thus excluded from consideration (n = 94). The final selection process resulted in the inclusion of 4 studies [18][19][20][21] in the review.…”
Section: Search and Selection Processmentioning
confidence: 99%
“…Table 2 presents a comprehensive overview of the key characteristics and assessments of the selected studies, [18][19][20][21] which collectively investigate the impact of probiotic supplementation on cognitive and related brain functions in patients with depression. Table 3 provides a comprehensive summary of the technical characteristics and key findings from the selected studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, clinical and animal studies have shown that probiotics supplementation could alleviate depression symptoms. In randomized, double-blind, placebo-controlled studies, probiotics significantly improved depression symptoms of depressive patients, though inconsistent results were reported concerning improvement of anxiety symptoms and serum inflammation markers ( 117 119 , 193 ). Animal studies indicated that the anti-depressive effect of probiotics may attribute to mitigating gut microbial dysbiosis ( 120 122 , 195 ), and this effect may not require the bacteria to be alive ( 112 ), suggesting a vital role of bacteria components in the effect.…”
Section: The Microbiota-gut-brain Axis and Depressionmentioning
confidence: 99%